(untitled) (Journal for the Study of Religion and History (JSRH), 2025)
The comparative study of religion has long occupied an uneasy position between claims of academic rigor and charges of subjectivity. Since its nineteenth-century origins in the comparative philology initiated by Max Müller, comparison has been alternately defended as the methodological core of religious studies and dismissed as an intellectual construct imposed by scholars. This thesis provides a historical and critical overview of the major comparative methodologies adopted by representative East–West comparative scholarship in the past five decades and asks why comparison continues to exert theoretical appeal despite persistent skepticism about its coherence. Engaging with scholars such as Robert Neville, Lee Yearley, Yao Xinzhong, Aaron Stalnaker, Julia Ching, David Hall, Roger Ames, and Michael Puett, the thesis analyzes their strategies for negotiating emic and etic perspectives, historical context, and conceptual translation. The discussion begins with Jonathan Z. Smith’s rejection of Mircea Eliade’s archetypal and universalizing categories. While Smith’s critique is often interpreted as a challenge to the legitimacy of comparison itself, this thesis argues that it instead opens a space for methodological renewal. The thesis then examines the emergence of a “new comparativism” in response to Smith, especially in the work of William Paden and Kimberley Patton, which reconceives comparison as reflexive and heuristic. Finally, this thesis argues that comparison entails both promise and risks, including decontextualization, analogical overreach, and the theological instrumentalization of religious objects and ideas. Hence, this thesis concludes that no single methodology can resolve the inherent tensions of comparison. Nevertheless, it is suggested that a viable comparative study of religion requires careful selection of categories, sensitivity to historical and cultural contexts, and a sustained balance between similarities and differences. If comparison remains “magical,” it is because it demands epistemic humility—the condition under which its power becomes self-restrained and intellectually responsible.